Assessment of Knowledge, Attitude and Breast Self-Examination Practice among Female Students in Sulaimani Polytechnic University - Masood Mohammed, Sarko (Kurdistan Journal of Applied Research, 2018)
Breast cancer is the most common cancer affecting women all over the world. it is estimated to account for around 25% of all malignant in women, and incidence shows continuously increasing trend in many countries all over the world. The aim of the study is to determine level of knowledge, awareness, and BSE practice for breast among SPU female students. A descriptive study was conducted a pre- tested questionnaire was used to determine knowledge, attitude and practices of female students in SPU regarding breast cancer and BSE. The face to face interview questionnaire was filled by systematic random sampling to 216 female students from 4 different colleges belongs to SPU, after getting verbal consent to participate voluntary in the study. Data were entered into Epi-data version 3.1.1 and exported to analyse in SPSS version 17. Descriptive analysis was performed and frequencies and percentages were reported. The mean age of participants was 20.7, the study result shows that the knowledge mean score of participants was 3.95 (SD ± 1.78).181(83.8%) have information of breast cancer, and 157(72.7%) have information on breast cancer sign,136(63.0%) have information on factor that increase change to get breast cancer,150(69.4%)have information on (BSE),86(39.8%)have information how to do (BSE),101(46.8%)have information on mammography .91(42.1%)practice of (BSE), only 10 ( 4.6 %) female students has performing this examination regularly , percentage of students that did not done mammography was 193 (89.4%) . only 2 (0.9 %) performs mammography screening regularly, 18 (8.3 %) have a family member that get breast cancer. Knowledge of female student about breast cancer was at unsatisfactorylevel. Knowledge of female student about S.B.E was also at unsatisfactory level. Poor practice was observed, regarding BSE. Knowledge regarding mammography was also poor.